Are cesarean delivery rates and indications changing? - Mane, Jitendra D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: There seems to be gradual raising trend in cesarean deliveries over decades with associated decrease in perinatal mortality rate. This study was undertaken to compare the caesarean delivery (CS) rates along with its indications over the last decade and to examine whether it is changing. Methods: The aim is to compare the rate and indications of CS in a retrospective manner from the data collected between January 1 and December 31 in the year 2006, 2011, and 2016 in a zonal hospital. The rates and indications of CS were analyzed to find whether they are changing if yes which are the factors contributing for the same. Categorical variables were compared using chi-square test. Results: The CS rate showed an increasing trend from 26 % in 2006 to 27.6 % in 2011 to 32.4 % in 2016. Of the total CS, repeat CS rate was significantly increased from 76 (6.61%) in 2006 to 106 (10.34%) in 2011 to 128 (13.72%). Primary CS percent remained more or less same during the study period. Post cesarean pregnancy (p=0.00001) and fetal distress (p=0.012) showed significant rise as an indication for CS which were major contributor for rise in last decade while failed induction decreased. Conclusions: Over the decade there is increase in the total CS rate mainly attributable to repeat CS while post CS pregnancies and foetal distress were leading cause for CS. There is need for reducing primary CS along with increase in trial of labor after cesarean in properly selected women.